Ethics of Finitude: Nursing and the Palliative Approach - Skinner, Elise (Université d'Ottawa / University of Ottawa, 2018)
Purpose: Within the contemporary socio-political context of palliative care and an aging demography, there is a called-for shift to an upstream provision of palliative care in the form of a palliative approach to care as well as to frame access to palliative care within a health equity perspective. In the literature, there is a paucity of nurses’ experiences in the provision of palliative care within psychiatric settings. Moreover, little is known of the process by which nurses engage in a palliative approach to care for patients experiencing multiple marginalities, including institutionalization, mental health, and advanced age. This research explored how nurses in forensic and geriatric psychiatry engage with aging patients and mortal considerations to discern how ethical dimensions of care, aligned within the palliative approach, are enacted. An ethical lens by which to apprehend dimensions of human finitude, reflective of central elements of the palliative approach and public health palliative care, was proposed to help to delineate a process of recognition through which values can be identified in the care of patients. The purpose of this thesis was to explore the phenomenon by which nurses engaged with mortality as both an antecedent to adopting a palliative approach and as a phenomenon that captures nurses’ continued engagement with patients within this approach. Objectives: There were three objectives to the project: 1) explore nurses’ engagement with mortality within an ethics of finitude; 2) identify enablers and barriers, and related historical and socio-political discourses, to engagement of nurses with their patients within an ethics of finitude, and; 3) articulate and deepen understanding of the palliative approach, including ethical dimensions and considerations. The research was an analytical elaboration of a qualitative study at the University of Ottawa that examined the palliative approach to nursing care in forensic and geriatric psychiatry at a mental health facility in eastern Ontario. Methods: Situated within a constructivist epistemic stance, the analytical framework elaborated for this analysis drew from both interpretive description (ID) and interpretive phenomenological analysis (IPA). Utilizing convenience sampling, eight Registered Nurses (7 women and 1 man) working in forensic or geriatric psychiatry completed interviews. Findings: Engagement of nurses within an ethics of finitude was revealed to surface through a process of recognition (recognition of mortality, recognition of the increased vulnerability of patients, and recognition of a corresponding increased responsibility for vulnerable patients) and through the affirmation of values including human connection, dignity, comfort, family, familiarity, and personhood. Barriers and enablers to this engagement emerged related to the care environment, the psychiatric nurse and patient construction, and factors related to family. The implications of the related discourses in the articulation of the palliative approach emerged in relation to health system considerations and to the language of the palliative approach. Conclusion: The process of recognition explored through the proposed ethical lens and revealed in the findings delineated values that underpin the palliative approach by offering an alternate conceptualization to their identification and enactment. Insights from this project underscore preliminary insights on a process to identify care practices aligned within the palliative approach as well as possibilities for critical questioning related to interconnected axes of an ethics of finitude in both the care of individual patients and in the enactment of health policy.
Keywords: palliative care; ethics; palliative approach; forensic